Roadmap of ecotourism development for emerging tourism destination in the Philippines / Ma. Gerlia Aujero-Blanza. - Aujero-Blanza, Ma. Gerlia (Universiti Teknologi Mara Selangor, 2019)
This study established an empirical data of the ecotourism in the Philippines focusing on the following destination sites in Region VI, a region in some part of the Western Visayas Area such as: Bakhawan Ecopark at Kalibo, Aklan, Municipality of Tibiao in Antique, Capiz Ecopark in Cuartero, Capiz, Taklong Island in Guimaras, and Mariit Ecopark in Lambunao, Iloilo. Specifically, the present investigation has delved looking into the status of ecotourism development, the extent of implementation of the Philippines National Ecotourism Strategy (NES), and the problems encountered in the above-mentioned sites. The survey questionnaire was randomly distributed to 384 respondents from the Department of Environment and Natural Resources (DENR), Department of Tourism (DOT) as well as tourist and residents within the focus areas. The study implemented the quantitative approach utilizing the mean, standard deviation, frequency distribution, and the rank as descriptive statistical tools. One-way Analysis of Variance (ANOVA) and Pearson’s Correlation Analysis were performed as inferential statistical tools. The results of the study pre-empted the formulation of a five-year roadmap for ecotourism development in Region VI, Western Visayas, Philippines.